PENGARUH KUALITAS PELAYANAN, PERSEPSI HARGA DAN FASILITAS TERHADAP KEPUASAN PASIEN DI STEPHANIE DENTAL - Raden Agustinus Randy Kelvianto; Elfrida Viesta Napitupulu (Sekolah Tinggi Pariwisata Mataram, 2022)
The authors are interested in examining the effect of service quality, price perception, and facilities on patient satisfaction at Stephanie Dental. The sample in this study were patients Stephanie Dental. Collecting data with a questionnaire and determining the sample by random sampling. The measuring tools used are validity test, reliability test, arithmetic mean, percentage analysis, scale range, classical assumption test, multiple regression analysis and interaction test using SPSS 25 application. The results of this study show the quality of service, price perception and facilities significant effect on patient satisfaction andrespondents were satisfied. The results of the interaction test between service-price perception, service-facility and facility-price perception on customer satisfaction indicate that these three variables have no interaction with patient satisfaction.